Effect of the number of coronavirus disease 2019 (COVID-19) vaccination shots on the occurrence of pneumonia, severe pneumonia, and death in SARS-CoV-2-infected patients - Xin, Shijun; Chen, Wei; Yu, Qilin; Gao, Li; Lu, Genjie (Frontiers in Public Health, 2024)
Background Coronavirus disease (COVID-19) has posed a significant threat to the lives and health of people worldwide since its onset in 2019. However, the relationship between the number of vaccination shots and the severity of SARS-CoV-2 infection in Chinese patients remains unclear. Methods We retrospectively collected information from 829 patients infected with SARS-CoV-2 in Ningbo Medical Center Lihuili Hospital from December 05, 2022 to March 31, 2023, then divided them into four groups based on the severity of pneumonia. Last, we compared the difference in the number of shots of COVID-19 vaccine between the four groups, considering potential confounding factors using univariate and multivariate logistic regression. Results Vaccination with two and three doses was positively associated with low prevalence of pneumonia and severe pneumonia both in crude and optimal models, while only three doses of the vaccine was correlated with low prevalence of death in SARS-CoV-2-infected patients. In optimal models, male SARS-CoV-2-infected individuals with advanced age were positively associated with high prevalence of pneumonia, severe pneumonia, and death; comorbidity with hypertension (OR = 2.532, p < 0.001) was positively associated with high prevalence of pneumonia (OR = 2.532, p < 0.001); and comorbidity with diabetes was positively associated with high prevalence of death (OR = 1.856, p = 0.011). However, this is a cross-sectional study and the causal relationships need to be further studied. Conclusion One dose of vaccine may not have a protective effect against pneumonia, severe pneumonia, and death; more than one dose of vaccine is an independent protective factor for pneumonia and severe pneumonia; and three doses of vaccine is an independent protective factor for death.